Kinetic turbulence in collisionless high-beta plasmas - Arzamasskiy, L; Kunz, MW; Squire, J; Quataert, E; Schekochihin, AA (American Physical Society, 2023)
We present results from three-dimensional hybrid-kinetic simulations of Alfvénic turbulence in a high- β , collisionless plasma. The key feature of such turbulence is the interplay between local wave-wave interactions between the fluctuations in the cascade and the nonlocal wave-particle interactions associated with kinetic microinstabilities driven by anisotropy in the thermal pressure (namely, firehose, mirror, and ion cyclotron). We present theoretical estimates for, and calculate directly from the simulations, the effective collisionality and plasma viscosity in pressure-anisotropic high- β turbulence, demonstrating that, for strong Alfvénic turbulence, the effective parallel-viscous scale is comparable to the driving scale of the cascade. Below this scale, the kinetic-energy spectrum indicates an Alfvénic cascade with a slope steeper than − 5 / 3 due to the anisotropic viscous stress. The magnetic-energy spectrum is shallower than − 5 / 3 near the ion-Larmor scale due to fluctuations produced by the firehose instability. Most of the cascade energy ( ≈ 80 % – 90 % ) is dissipated as ion heating through a combination of Landau damping and anisotropic viscous heating. Our results have implications for models of particle heating in low-luminosity accretion onto supermassive black holes, the effective viscosity of the intracluster medium, and the interpretation of near-Earth solar-wind observations.